International Crime Victim Survey (ICVS), 1989-1997 - Alvazzi del Frate, Anna ([Verlag nicht ermittelbar], 2001)
The International Crime Victim Survey (ICVS) was a far-reaching program of standardized sample surveys that investigated householders' experiences with crime, policing, crime prevention, and perceptions of safety. The surveys were carried out in the following countries: Albania, Argentina, Australia, Austria, Belarus, Belgium, Bolivia, Botswana, Brazil, Bulgaria, Canada, Chechnia, China, Colombia, Costa Rica, Croatia, Egypt, England and Wales, Estonia, Finland, France, Georgia, Germany (West), Hungary, India, Indonesia, Italy, Japan, Kyrgyzstan, Latvia, Lithuania, Macedonia, Malta, Mongolia, the Netherlands, New Zealand, Northern Ireland, Norway, Paraguay, the Philippines, Poland, Rumania, Russia, Scotland, Slovakia, Slovenia, South Africa, Spain, Sweden, Switzerland, Tanzania, Tunisia, Uganda, Ukraine, the United States, Yugoslavia, and Zimbabwe. The data were collected in three waves: 1989, 1992-1994, and 1995-1997. The main focus of the ICVS was whether the respondent was a victim of theft of or from vehicles, other thefts, vandalism, robbery, pickpocketing, sexual harassment or violence, or assault. The surveys also investigated the frequency of victimization, reasons for not reporting a crime to the police, familiarity with the offender in the case of a sexual offense, physical violence, injuries, fear of crime in the respondent's local area, use of help agencies for victims, satisfaction with police behavior, preferred legal sanctions, punishment, and length of detention for offenders, safety precautions when leaving home, possession of a gun, burglar alarm, or insurance, and frequency of going out.